Indonesia Economic Quarterly, June 2018 : Learning More, Growing Faster - World Bank (World Bank, Washington, DC, 2018)
This edition includes a focus topic that discusses how 15 years of education reforms have helped to improve education outcomes and human capital in Indonesia, and what challenges remain. The outcomes from 15 years of educational reform have been mixed, with a significant expansion inaccess, but a large deficit in quality. In 2002, Indonesia embarked on a series of policy reforms to strengthen access to and the quality of education, both key determinants of human capital development. After 15 years, however, the results of the reforms have been mixed. Enrolments have grown significantly, but student learning remains below the levels of other countries in the region. For example, 55 percent of 15-year olds are functionally illiterate, compared to lessthan 10 percent in Vietnam. Education reform covered the right areas, but implementation challenges led to uneven results. Most elements of the reforms were aligned with international best practices and had strong potential to improve Indonesian education outcomes. Educationreform included increasing financing for education, enhancing participation of local actors in sector governance, strengthening accountability, improving the quality of teachers, and ensuring students’ preparedness as they enter schooling. Significant implementation challenges prevented the policy reform from reaching its full potential. While steps have been taken to address some ofthese challenges, further actions are urgently needed. In particular, measures need to be taken tostop growing inequality in student results, and to take advantage of the opportunity generated by the large number of teachers retiring in the next decade. Key recommendations include: defining and enforcing qualification criteria to be met by every teacher who enters the classroom, complementing the existing financing mechanisms for education with a targeted, performance-based transfer for lagging schools and districts, and launching a national education quality campaign to generate public awareness and pressure for effective action to improve student learning.